Î²-Glucans Production of Saccharomyces cerevisiae by Using Tofu Waste as Animal Feed Supplement - Sulistya Dewi, Endah Rita; Nugroho, Ary Susatyo; Nurwahyunani, Atip; Ulfah, Maria (Biosaintifika: Journal of Biology & Biology Education, 2021)
Tofu industrial waste has the potential to become contaminant when it is not maximum processed, so it needs appropriate treatment to minimize the occurrence of pollution. Î²-Glucans can be produced from the yeast cell wall of Saccharomyces cerevisiae.As a feed supplement, Î²-Glucans have been used for an immunostimulant because it can increase the immune system. This study aimed to establish a suitable technology to produce Î²-Glucans fromSaccharomyces cerevisiae by utilize tofu waste as feed supplement. The Completely Randomized Design (CRD) model was used in the experimental method. This study used an experimental method with a Completely Randomized Design (CRD) model.The treatment given wereP1: 1kg of tofu waste + 1kg of bran +0.2 kg fish meal + 0.2 lt molasses + 5.5 gSaccharomyces cerevisiae; P2: 1kg of tofu waste + 1kg of bran +0.2 kg fish meal + 0.2 lt molasses + 6.5 g Saccharomyces cerevisiae; P3: 1kg of tofu waste + 1kg bran + 0.2 kg fish meal +0.2 lt molasses + 7.5 g Saccharomyces cerevisiae. Each treatment was repeated 3 times, and fermented for five days.The results found that P1 by Saccharomyces cerevisiae 5.5 g was the best formulation to produced crude Î²-Glucans by weight of 25.9 g/kg of waste. Production of Î²-Glucans as an animal feed supplement is a waste-based feed technology development which is expected to increase livestock production both in quality and quantity.